Fiscal Objective in the Post IMF Program World : The Case of Albania - Jonas, Jiri. (Washington, D.C. : International Monetary Fund, 2010)
The paper discusses the challenges facing Albania's fiscal policy following the graduation from the IMF programs. It argues that Albania's public debt remains too high and needs to be reduced. Strengthening the fiscal framework, including by introducing a numerical fiscal rule, could help achieve this objective. The paper discusses two alternative rules, with the objective of achieving a gradual decline in the public debt ratio. One rule would limit nominal expenditure growth, with a correction mechanism to guard against revenue slippages and other shocks. An alternative rule would limit the growth in nominal public debt.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet